APPLICATION OF PROJECT BASED LEARNING (PjBL) LEARNING MODEL TO IMPROVE SELF-LEARNING AND RESULTS LEARNING COURSES (Study on LKP ADELLA in Kepahiang Regency) - Debi Vanhoten; Riyanto Riyanto (DIADIK, 2018)
This study aims to describe the increasing independence and learning outcomes of sewing course participants who took part in the PKK program at ADELLA LKP by applying the Project Based Learning (PjBL) learning model. The research method applied is collaborative classroom action research. The subjects of this study were sewing courses participants at ADELLA LKP Kepahiang District who participated in PKK program the 2018 as many as 20 participants. Data collection techniques are carried out through activities in the form of: (a) observation; (b) test. Research procedures include stages: (a) action planning, (b) implementation of actions, (c) observation and interpretation, and (d) analysis and reflection. The analysis technique uses descriptive analysis. Based on the results of the study showed that the learning independence and learning outcome of the course participants had increased. It is expected that the instructors can try and apply a more varied Project Based Learning (PjBL) model because this learning model can be applied to the course institutions.